Social Virtual Reality Platform Comparison and Evaluation Using a Guided Group Walkthrough Method - Liu, Qiaoxi; Steed, Anthony (Frontiers in Virtual Reality, 2021)
As virtual reality (VR) headsets become more commercially accessible, a range of social platforms have been developed that exploit the immersive nature of these systems. There is a growing interest in using these platforms in social and work contexts, but relatively little work into examining the usability choices that have been made. We developed a usability inspection method based on cognitive walkthrough that we call guided group walkthrough. Guided group walkthrough systematise the comparison of existing social VR platforms by having a guide walk the participants through a series of abstract social tasks that are common across the platforms. We compared six social VR platforms for the Oculus Quest. After constructing an appropriate task hierarchy and walkthrough question structure for social VR, we ran several groups of participants through the walkthrough process. We undercover usability challenges that are common across the platforms, identify specific design considerations and comment on the utility of the walkthrough method in this situation.